2020
DOI: 10.1108/jkm-03-2020-0234
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise social media usage and knowledge hiding: a motivation theory perspective

Abstract: Purpose Reducing employees’ knowledge hiding is vital for enterprise managers. The development of enterprise social media brings opportunities for them to manage employees’ knowledge-hiding behaviors. However, whether the use of enterprise social media inhibits or promotes knowledge hiding is still unclear. The purpose of this study is to explore how enterprise social media usage affect employees' knowledge hiding. Design/methodology/approach Based on the intrinsic and extrinsic motivation model, this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 47 publications
(95 reference statements)
1
56
0
Order By: Relevance
“…Previous studies have sought to develop a research model that integrates motivational characteristics [16,23], the big five personality types [12], and leadership styles that influence knowledge hiding [24]. We assume that one of the major causes of knowledge hiding is relationship conflict, which creates aggressiveness in the personality and eventually leads to knowledge hiding.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have sought to develop a research model that integrates motivational characteristics [16,23], the big five personality types [12], and leadership styles that influence knowledge hiding [24]. We assume that one of the major causes of knowledge hiding is relationship conflict, which creates aggressiveness in the personality and eventually leads to knowledge hiding.…”
Section: Introductionmentioning
confidence: 99%
“…Their research expands the theoretical line of affordances of ESM by clarifying that the affordances allow for both openness and ambiguity in knowledge sharing. Ma et al (2020) found that socially related ESM usage has a promoting effect on employees' knowledge hiding.…”
Section: Analysis Of Landmark Research In the Esm Literaturementioning
confidence: 99%
“…Managers may be made aware of this through any number of organizational communication channels such as company handbooks, memos, and even formal training and leadership development programs. One way organizations can ensure effective communication among managers and employees is to adopt and diffuse communication technologies such as social media that ease the barriers of communication and reduce the risk of knowledge hiding at different top-down and bottom-up levels (Biswas et al, 2013;Ma et al, 2020). They also need to monitor the quality of this essential relationship through their ongoing communications, annual performance reviews, and other mechanisms such as annual staff surveys (Graen and Uhl-Bien, 1995).…”
Section: Practical Implicationsmentioning
confidence: 99%